Critical positions: Situating critical perspectives in work and organizational psychology. (February 2022) - Islam, Gazi; Sanderson, Zoe
This paper argues that critical perspectives have constituted a marginal yet continued presence in work and organizational (W-O) psychology and calls for a reflexive taking stock of these perspectives to ground a critical research agenda. We argue that critical W-O psychology has been positioned between a psychology literature with limited development of critical perspectives, and an emergent critical management literature that has allowed their selective development. This in-between position has allowed critical W-O psychology to persist, albeit in a fragmented form, while limiting its potential for theoretical and applied impact. We use this diagnosis to reflect on how critical perspectives can best develop from within W-O psychology. We end with a call for developing a critical movement unique to the current historical moment, drawing upon without repeating the experiences of its home disciplines, in a future oriented and reflexive psychology research agenda.